Tetron Bay, Trinidad, B.W.I. - (:unkn) unknown (My University, 2011)
An aerial view of Tetron Bay which was once host to holiday resorts, vacations and family homes. The picture show a jetty and structures along the shoreline and houses scattered among the green forested area of the hills.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Tetron Bay; Bays--Trinidad and Tobago; Boats and boating